"Internal envelope", a practical exploration of contemporary interior space regenerated in traditional buildings. Issue 1 (2nd January 2021) - Guo, Li; Zhao, Chen
ABSTRACT: Reviving historical towns and urban districts requires conservation and reuse of traditional buildings crucially in preserving the external form while introducing contemporary contents into the interior spaces. Short of contemporary comfort and efficiency, the traditional interior unavoidably contradicts the preservation for according improvement of comfort as the crux. Setting out from construction rule and characteristics of the traditional Chinese architecture with reference to its European counterpart's "envelope" feature, we propose "internal envelope" as a new interior implanted into the traditional interior, a freestanding container of self-bearing framework of up-to-date techniques that accommodates all needs from office, residence to recreation. In ensuing practices, the "internal envelope" successively applied in a series of cases in the historical town of Cicheng, Ningbo, and each case designed in response to specific structure and scale of the courtyard and interior to ensure the desired comfort. As the representative one, Cihu Academy attested "internal envelope" thorough and successful realization from conception, scheme, construction to put into service, a full course that demonstrated its validity in its own right as well as significance to architecture the discipline in sound response to targeted problems. Graphical Abstract: uf0001